Power generation of small wind turbine: Under high-speed operation - M. Saad, Magedi Moh; Mohd, Sofian; Zulkafli, Mohd Fadhli (Elsevier, 2018)
Mechanical energy is produced through the rotation of wind turbine blades by air that converts mechanical energy into electrical energy. Wind turbines are usually designed for particular applications, and design characteristics may vary depending on the area of use. The variety of applications is reflected on the size of turbines and their infrastructures. Wind turbine performance may be enhanced by analyzing the small horizontal axis wind turbine (SHAWT) under high-wind-speed operation. This work analyzes the implementation of the SHAWT and investigates its performance in simulation and real life. The power performance of the SHAWT, which largely depends on the real structure of the rotor geometry and aerodynamic test, was simulated using ANSYS Fluent software at different wind speeds of up to 33.33 m/s (120 km/h) to numerically investigate actual turbine operation. Dynamic mesh and user-defined function (UDF) were used to revolve the rotor turbine via wind. Simulation results were further validated by experimental data, and good matching was achieved. A car alternator was formed and used as a small horizontal wind turbine to reduce energy production cost. Consequently, the alternator-based turbine system was found to be a low-cost solution for the exploitation of wind energy.